Dekadensi Moral dan Kaitannya Dengan Pendidikan Agama Islam - Arya Bisma Nugraha; Muhammad Taufik; Muhammad Nasir (STIKes Ibnu Sina Ajibarang, 2024)
Islamic religious education plays a crucial role in shaping the noble character of the younger generation. This research aims to investigate the role of Islamic religious education in shaping the noble character of the younger generation. The research method used is qualitative method with data collection techniques through observation, interviews, and documentary studies. The results of the research show that Islamic religious education plays an important role in shaping the noble character of the younger generation through understanding moral concepts, controlling oneself and emotions, fostering a strong work ethic and discipline, developing empathy and respecting others, as well as raising awareness of the importance of preserving the environment and nature. However, the research also identifies several challenges in the implementation of Islamic religious education, such as the lack of resources and support for Islamic religious education programs. Therefore, several recommendations are proposed to improve the effectiveness of Islamic religious education in shaping the noble character of the younger generation, including the development of a more effective curriculum, training and mentoring for Islamic religious teachers, increased support from parents and the community, as well as increased resources and support for Islamic religious education programs.